Synthesis, Characterization, Mössbauer Parameters, and Antitumor Activity of Fe(III) Curcumin Complex - Mutasim Ibrahim Khalil; Aisha Mohamed Al-Zahem; Maha Hamad Al-Qunaibit (Bioinorganic Chemistry and Applications)
Curcumin-Fe(III) complex was prepared from Fe(NO3)3·9H2O precursor and curcumin by refluxing a slightly basic methanolic solution of their mixture with the objective of investigating its cytotoxicity. The enol form of curcumin ligand was established by FTIR, UV/Vis, 1H NMR, and 13C NMR spectroscopy. The as-prepared product was characterized by elemental analysis, FTIR, UV, and Mössbauer spectroscopic techniques. An octahedral high-spin Fe(III) complex was obtained, δ, 0.37 mms−1; Q.S., 0.79 mms−1; no magnetic relaxation was observed at liquid N2 temperature, neither reduction of Fe(III). The tested cytotoxicity of the as-prepared complex on four cancer cell lines indicated inhibition of the curcumin activity upon complexing with iron.